PERANAN BANK SAMPAH TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT DALAM TINJAUAN PERSPEKTIF MAQASHID SYARIAH - Natzmi, Alvi; Marliyah, Marliyah; Dharma, Budi (MediaTrend, 2024)
This research aims to describe the role of the Berkah waste bank in Cinta Makmur Village in empowering the community’s economy from a maqashid sharia perspective. The research uses qualitative methods by means of field observations, interviews with related sources and is supported by several sources such as books, journals and other documents. The results of this research show an increase in fulfilling basic needs, increasing income, increasing independence, and environmental cleanliness. The mechanism for managing the Berkah waste bank is that the community collects their waste, it is collected by the waste bank team, then weighed and recorded in a book. After that, the waste bank team sorts the waste and then sells it to collectors. The role of the Berkah waste bank is very good in managing and sorting waste into goods. which has economic value, so that it can improve the economy of its customers. Islam also teaches us to always maintain cleanliness, with the formation of this waste bank cleanliness begins to be fulfilled. This research has limitations, including that the researcher is limited to observing the running process of the waste bank at any time because the waste bank program schedule is irregular due to officers not being able to regularly pick up the waste. Apart from that, this research is limited to examining the role of the waste bank in empowering the community in improving the economy. and researchers limited the research area to Cinta Makmur Village.